2023
DOI: 10.3346/jkms.2023.38.e203
|View full text |Cite
|
Sign up to set email alerts
|

The Association Between Blood Lead Levels and Coronary Artery Calcium Score Determined by Using Coronary Computed Tomography Angiography

Abstract: Background Lead exposure is a known risk factor for cardiovascular disease (CVD), and coronary artery calcification (CAC) is a biomarker for diagnosing atherosclerotic CVD. This study investigated the association between blood lead level (BLL) and CAC using coronary computed tomography (CT) angiography. Methods This study enrolled 2,189 participants from the general population with no history or symptoms of CVD. All participants underwent coronary CT angiography, health… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 37 publications
0
0
0
Order By: Relevance
“…A newly published cross-sectional study using data from the population-based Swedish CardioPulmonary bioImage Study (SCAPIS) [ 205 ], including 5622 middle-aged men and women, found blood lead levels to be associated with an 8% increased risk of carotid artery plaque, as a predictive marker of clinical atherosclerosis. These results are in line with other studies showing an association between body lead levels and different markers of atherosclerosis, like coronary artery calcification [ 206 ] and intima–media thickness (IMT) [ 207 ]. The systematic review and meta-analysis of Chowdhury et al [ 208 ] explored the link between cardiovascular disease risk and toxic metals.…”
Section: Toxic Metals In Foodsupporting
confidence: 92%
“…A newly published cross-sectional study using data from the population-based Swedish CardioPulmonary bioImage Study (SCAPIS) [ 205 ], including 5622 middle-aged men and women, found blood lead levels to be associated with an 8% increased risk of carotid artery plaque, as a predictive marker of clinical atherosclerosis. These results are in line with other studies showing an association between body lead levels and different markers of atherosclerosis, like coronary artery calcification [ 206 ] and intima–media thickness (IMT) [ 207 ]. The systematic review and meta-analysis of Chowdhury et al [ 208 ] explored the link between cardiovascular disease risk and toxic metals.…”
Section: Toxic Metals In Foodsupporting
confidence: 92%